2011
DOI: 10.1371/journal.pone.0023457
|View full text |Cite
|
Sign up to set email alerts
|

A One-Step Miniprep for the Isolation of Plasmid DNA and Lambda Phage Particles

Abstract: Plasmid DNA minipreps are fundamental techniques in molecular biology. Current plasmid DNA minipreps use alkali and the anionic detergent SDS in a three-solution format. In addition, alkali minipreps usually require additional column-based purification steps and cannot isolate other extra-chromosomal elements, such as bacteriophages. Non-ionic detergents (NIDs) have been used occasionally as components of multiple-solution plasmid DNA minipreps, but a one-step approach has not been developed. Here, we have est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…Our current experience in DNA extraction and purification suggests that sample preparation in the liquid state is the most time and cost‐efficient approach. In particular, changing water properties including solutes solubility by the addition of salts, detergents, and organic solvents could replace expensive solid mass exchange resins with lengthy processing times . Consistent with this notion, we studied whether PCR products could be precipitated from iPrOH solutions of LiCl, a salt highly soluble in alcohol, simultaneously retaining 100‐200 bp PCR byproducts in the solutions.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Our current experience in DNA extraction and purification suggests that sample preparation in the liquid state is the most time and cost‐efficient approach. In particular, changing water properties including solutes solubility by the addition of salts, detergents, and organic solvents could replace expensive solid mass exchange resins with lengthy processing times . Consistent with this notion, we studied whether PCR products could be precipitated from iPrOH solutions of LiCl, a salt highly soluble in alcohol, simultaneously retaining 100‐200 bp PCR byproducts in the solutions.…”
Section: Resultsmentioning
confidence: 94%
“…The pattern of native plasmid DNA bands, formed in electrophoresis gels, partially depends on the DNA extraction method's capacity to inhibit intracellular endonucleases and topoisomerases. Unlike alkali extraction, NID buffers lacking inhibitors allow the extraction of sensitive lambda particles and the use of NID crude extracts for downstream applications . Thus, a difference in gel banding plasmid DNA extracted by alkali and NID is expected as it is shown in Figure A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using "area" and "label peaks" commands, the percentage of the area of each band can be calculated. This technique has been employed to conduct image analysis in several studies [10,[27][28][29].…”
Section: Agarose Gel Electrophoresis Analysismentioning
confidence: 99%
“…Lezin et al [10], developing a one-step approach for isolate pDNA, found that non-ionic detergent (NID) plasmid DNA performs better than alkaline treatment in many downstream applications. Bag et al [11] developed an improved method for the extraction of community DNA from different environmental and human origin samples by a combination of physical, chemical, and mechanical lysis methods for proper lysis of microbial DNA.…”
Section: Introductionmentioning
confidence: 99%